IMPLEMENTASI FUZZY TERHADAP SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN KELAYAKAN PEMBIAYAAN PENGAJUAN KREDIT BARANG - Septilia Arfida (Jurnal Informatika, 2012)
PT. X is a company which operates in electronics and furniture financing. As a finance company, the major concern is how to get as many debtors who have a strong commitment to repay provided financing. Decision Support System is one of the uses of computer technology which is able to help in a decision making. The loan officers are required precision, accuracy and responsibility in determining the admissibility of such financing in order to the management of PT. X wills not loss. One way to determine a accepted or not accepted financing is by building up a system that can facilitate the management in assessing of feasibility of the filling of financing by debtors using Fuzzy Inference System Mamdani method. It is known that by Fuzzy Inference System Mamdani method implementation will simplify for the management in financing decision making whether receive or not from debtors’ filing.Keyword: Fuzzy Inference System, Mamdani Method, Filling of credit